Unexpected Salt/Cocrystal Polymorphism of the Ketoprofen-Lysine System: Discovery of a New Ketoprofen-l-Lysine Salt Polymorph with Different Physicochemical and Pharmacokinetic Properties - Andrea Aramini; Gianluca Bianchini; Samuele Lillini; Simone Bordignon; Mara Tomassetti; Rubina Novelli; Simone Mattioli; Larisa Lvova; Roberto Paolesse; Michele Remo Chierotti; Marcello Allegretti (MDPI AG, 2021)
Ketoprofen-l-lysine salt (KLS) is a widely used nonsteroidal anti-inflammatory drug. Here, we studied deeply the solid-state characteristics of KLS to possibly identify new polymorphic drugs. Conducting a polymorph screening study and combining conventional techniques with solid-state nuclear magnetic resonance, we identified, for the first time, a salt/cocrystal polymorphism of the ketoprofen (KET)-lysine (LYS) system, with the cocrystal, KET-LYS polymorph 1 (P1), being representative of commercial KLS, and the salt, KET-LYS polymorph 2 (P2), being a new polymorphic form of KLS. Interestingly, in vivo pharmacokinetics showed that the salt polymorph has significantly higher absorption and, thus, different pharmacokinetics compared to commercial KLS (cocrystal), laying the basis for the development of faster-release/acting KLS formulations. Moreover, intrinsic dissolution rate (IDR) and electronic tongue analyses showed that the salt has a higher IDR, a more bitter taste, and a different sensorial kinetics compared to the cocrystal, suggesting that different coating/flavoring processes should be envisioned for the new compound. Thus, the new KLS polymorphic form with its different physicochemical and pharmacokinetic characteristics can open the way to the development of a new KET-LYS polymorph drug that can emphasize the properties of commercial KLS for the treatment of acute inflammatory and painful conditions.